An investigation of associations between experience of childhood trauma and political violence and theory of mind impairments in schizophrenia. (December 2018) - Kincaid, Debbie; Shannon, Ciaran; Boyd, Adrian; Hanna, Donncha; McNeill, Owen; Anderson, Rick; Francis-Naylor, Michelle; Mulholland, Ciaran
Highlights: Theory of Mind impairments are a significant feature of schizophrenia. This study found that emotional neglect, specifically during early childhood (0–6 years) predicted theory of mind impairments in this group. Conflict-related trauma was also associated with theory of mind but was not an independent significant predictor of these deficits. Exposure to emotional neglect may preclude or reduce opportunities for communication of mental state understanding from caregivers and therefore may result in difficulties forming mental representations, which is required for effective theory of mind. Abstract: There has been little examination of the association between trauma and cognitive deficits seen in individuals diagnosed with schizophrenia. Theory of Mind (ToM) impairments are a significant feature of schizophrenia but it remains unclear as to why these deficits are so prevalent in this population. This study aimed to explore associations between ToM deficits and specific forms of childhood adversities in a schizophrenia population. The study sample comprised of 66 adults with a confirmed diagnosis of schizophrenia, attending mental health services in Northern Ireland. Assessments were completed to ascertain if individuals had prior experience of sexual or physical abuse, emotional neglect or experience of the political violence of Northern Ireland's "Troubles", and the Gardner Hinting Test was applied to assess ToM ability. Backwards stepwise regression analyses demonstrated that emotional neglect, specifically during early childhood (0–6 years) predicted ToM impairments in this group. Conflict-related trauma was also associated with ToM but was not an independent significant predictor of ToM deficits. This is the first study to examine links between specific forms of childhood adversity and ToM impairments in individuals diagnosed with schizophrenia. Potential underpinning psychological mechanisms are considered and implications for clinical practice are discussed.